Modern Practices of Vaccination of Children from Perinatal Risk Groups and Necessary Precaution - O. A. Kuznetsova; A. A. Golubkova; N. V. Bashmakova (Эпидемиология и вакцинопрофилактика, 2020)
Relevance. In perinatal centres problems of timely vaccination of newborns arise more often than in maternity hospitals, as vaccinations against viral hepatitis B and tuberculosis in accordance with the National Calendar are carried out in an early neonatal period and in time coincide with the stage of treatment and rehabilitation of the newborn, which implies medical withdrawal from vaccination. Vaccination of newborns from high perinatal risk groups is one of the problems of modern vaccinology and immunology.Aims. On the basis of clinical and immunological characteristics of postnatal babies from mothers with gestational diabetes and fetoplacental insufficiency justify the necessity and safety of their vaccination in the maternity hospital of the perinatal center.Materials & Methods. A cohort retrospective case-control study was conducted, and 135 birth and developmental history and newborn disease were analyzed. Statistical processing was carried out package «Statistica».Results. The main nosological forms of pathology in maternity mothers and their newborn children, the volume of primary vaccination (against viral hepatitis B, tuberculosis) in maternity hospital in children with perinatal pathology and healthy newborns have been determined, and the reasons for medical contraindications to vaccinations against viral hepatitis B and tuberculosis have been established.Conclusions. Newborns from high perinatal risk groups can be vaccinated against viral hepatitis B and tuberculosis in the maternity hospital within the time frame specified by the National Calendar of Preventive Vaccinations. In addressing this issue, the fundamental criteria are to assess the clinical condition of newborns from women with gestational diabetes and fetoplacental insufficiency. Changes in immunological values of umbilical cord blood and in children of 1 month of life are not a criterion for medical withdrawal from vaccinations against viral hepatitis B and tuberculosis.